Increased species-assignment of filamentous fungi using MALDI-TOF MS coupled with a simplified sample processing and an in-house library. (9th February 2018) - Zvezdanova, M E; Escribano, P; Ruiz, A; Martínez-Jiménez, M C; Peláez, T; Collazos, A; Guinea, J; Bouza, E; Rodríguez-Sánchez, B
Abstract: In this study we evaluated the capacity of MALDI-TOF MS (Bruker Daltonics, Bremen, Germany) to identify clinical mould isolates. We focused on two aspects of MALDI-TOF MS identification: the sample processing and the database. Direct smearing of the sample was compared with a simplified processing consisting of mechanical lysis of the moulds followed by a protein extraction step. Both methods were applied to all isolates and the Filamentous Fungi Library 1.0 (Bruker Daltonics) was used for their identification. This approach allowed the correct species-level identification of 25/34 Fusarium spp. and 10/10 Mucor circinelloides isolates using the simplified sample processing. In addition, 7/34 Fusarium spp. and 1/21 Pseudallescheria/Scedosporium spp. isolates were correctly identified at the genus level. The remaining isolates–60–could not be identified using the commercial database, mainly because of the low number of references for some species and the absence of others. Thus, an in-house library was built with 63 local isolates previously characterized using DNA sequence analysis. Its implementation allowed the accurate identification at the species level of 94 isolates (91.3%) and the remaining nine isolates (8.7%) were correctly identified at the genus level. No misidentifications at genus level were detected. In conclusion, with improvements of both the sample preparation and the feeding of the database, MALDI-TOF MS is a reliable, ready to use method to identify moulds of clinical origin in an accurate, rapid, and cost-effective manner.